TREATMENT OF EARLY SYPHILIS WITH CEPHALORIDLNE ENGL SUM - MORENO, JUAN B; GONZALEZ OCHOA, ANTONIO (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1894)
Forty patients with early syphilis, with Trepo-nema present in the lesions, were selected for this study 7 groups of 5 patients each, were treated with cephaloridine under 7 Thirty five, divided into different therapy schemes; an 8th group also of 5 pa
REV INVEST SALUD PUBLICA
Keywords: TREATMENT, SYPHILIS, CEPHALORIDLNE; CIENCIAS MEDICAS; MEDICINA INTERNA; ENFERMEDADES INFECCIOSAS